Effect of Nd:YAG Laser with/without Graphite Coating on Bonding of Lithium Disilicate Glass-Ceramic to Human Dentin - Amjad Abu Hasna; Stephanie Semmelmann; Fernanda Alves Feitosa; Danilo De Souza Andrade; Franklin R Tay; Cesar Rogério Pucci (International Journal of Dentistry)
This study evaluated the effect of different surface treatments on the tensile bond strength between lithium disilicate glass-ceramics, resin cement, and dentin. Fifty truncated cone-shape glass-ceramics were divided into five groups (n = 10): G1, control: 10% hydrofluoric acid (HF); G2, Nd:YAG laser + silane; G3, Sil + Nd:YAG laser; G4, graphite + Nd:YAG laser + Sil; and G5, graphite + Sil + Nd:YAG laser. Fifty human third-molars were cut to cylindrical shape and polished to standardize the bonding surfaces. The glass-ceramic specimens were bonded to dentin with a dual-cured resin cement and stored in distilled water for 24 h at 37ºC. Tensile testing was performed on a universal testing machine (10 Kgf load cell at 1 mm/min) until failure. The bond strength values (mean ± SD) in MPa were G1 (9.4 ± 2.3), G2 (9.7 ± 2.0), G3 (6.7 ± 1.9), G4 (4.6 ± 1.1), and G5 (1.2 ± 0.3). Nd:YAG laser and HF improve the bond strength between lithium disilicate glass-ceramics, resin cement, and dentin. The application of a graphite layer prior to Nd:YAG laser irradiation negatively affects this bonding and presented inferior results.